IMPLEMENTASI KEGIATAN CERITA KISAH BERHIKMAH DALAM PEMBINAAN AKHLAK ANAK USIA DINI DI TKTQ AL-KHANSA - Adwiah, Amalia; Ririn Duwila; Nur Istiana Makarau; Arsyia Fajarrini (Institut Agama Islam Negeri Bone, 2025)
This study aims to describe the implementation of Islamic storytelling in the moral development of early childhood at the TKTQ AL-KHANSA. The background of this study stems from the importance of instilling moral values from an early age as a foundation for developing children's noble character. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that structured and consistent Islamic storytelling activities can foster positive behaviors in children, such as politeness, honesty, responsibility, empathy, and the ability to control emotions. The changes in children's attitudes were not only observed in the school environment but also directly felt by parents at home. This indicates that the Islamic storytelling method is effective in internalizing moral and spiritual values in a fun and developmentally appropriate way. Therefore, this approach is worthy of integration into the learning process at early childhood education institutions more broadly.